Korelasi Dan Analisis Lintas Komponen Komponen Hasil Kedelai Famili F6 Hasil Persilangan Wilis X B3570 - Saputra, Tibor Eka; Barmawi, Maimun; Ermawati, Ermawati; Sa`diyah, Nyimas (Jurnal Penelitian Pertanian Terapan, 2016)
Soybean is an alternative stapple food which use by all people in Indonesia. However,domestic soybean production does not meet the needs of the national soybean. To meetthe needs done, it important to assemble the soybean breeding to improved the noblevarieties. Plant breeding is largely determined by the ability of breeders to select.Selection can be done by estimating the correlation coefficient between thecomponents of the results and outcomes. To determine the causal relationship betweenyield and yield components used path analysis. Path analysis of correlation coefficientwill break into the direct and indirect influence. The purpose of this study are todetermine (1) the correlation between the components of the results and outcomes; (2)direct and indirect influence between the components of the results and outcomes. Theexperiment was conducted from March to July 2014 in field trials of POLINELA(Lampung State Polytechnic) and in Seed Laboratory of University of Lampung.Soybean seed used is the result of crossing Wilis F6 generation x B3570. Treatmentarranged in a perfect randomized group design with two replications. The results ofcorrelation analysis showed correlation great and positive value indicated by thecomponent total number of pods per plant and grain weight per plant (0.80 *),hundred grain weight and grain weight per plant (0.72 *), and the number ofproductive branches and grain weight per plant (0.57 *). Results of the analysisshowed cross large direct effect on the character of the total number of pods per plantto grain weight per plant (0.89), which is almost as large as the correlation (0.80 *).Then the correlation coefficient was actually measure the degree of closeness of theirrelationship. Therefore, the selection is based on the total number of pods will be veryeffective to get genotype expectations that have high yields.Keywords: Soybean, Selection, correlation, analysis of cross